The kinetics of neutrophils in photodynamic theraphy as anti-tumor - Amalina, M. A.; Zulaziz, Natasha; Ho, Cassandra; Azhim, Azran; Horiuchi, Toshikatsu; Miyazaki, Hiromi; Saito, Daizoh; Himeno, Naomi; Kinoshita, Manabu; Shinomiya, Nariyoshi; Morimoto, Yuji (2015)
Photodynamic therapy (PDT) is known for its antitumor property. PDT uses a photosensitizer combined with light to kill cancer cells. Different to other non-surgical cancer treatments such as chemotherapy and radiotherapy which suppress immune system, it is suggested that PDT promotes an accumulation of neutrophils causing destruction of tumor cells; however, this is not be fully elucidated. Neutrophils is known to be a main player in the innate immunity and is closely related to the inflammation of the tumor site after PDT. Therefore, in this research, we investigated the relationship of neutrophils kinetics and anti-tumor property of PDT.